Species richness effects on grassland recovery from drought depend on community productivity in a multisite experiment. (20th September 2017) - Kreyling, Juergen; Dengler, Jürgen; Walter, Julia; Velev, Nikolay; Ugurlu, Emin; Sopotlieva, Desislava; Ransijn, Johannes; Picon‐Cochard, Catherine; Nijs, Ivan; Hernandez, Pauline; Güler, Behlül; von Gillhaussen, Philipp; et al.
Abstract: Biodiversity can buffer ecosystem functioning against extreme climatic events, but few experiments have explicitly tested this. Here, we present the first multisite biodiversity × drought manipulation experiment to examine drought resistance and recovery at five temperate and Mediterranean grassland sites. Aboveground biomass production declined by 30% due to experimental drought (standardised local extremity by rainfall exclusion for 72–98 consecutive days). Species richness did not affect resistance but promoted recovery. Recovery was only positively affected by species richness in low‐productive communities, with most diverse communities even showing overcompensation. This positive diversity effect could be linked to asynchrony of species responses. Our results suggest that a more context‐dependent view considering the nature of the climatic disturbance as well as the productivity of the studied system will help identify under which circumstances biodiversity promotes drought resistance or recovery. Stability of biomass production can generally be expected to decrease with biodiversity loss and climate change.